Numerical study of the dynamic response of a wind turbine on a tension leg platform with a coupled partitioned six degree-of-freedom rigid body motion solver - Chow, Jeng Hei (2019)
In assessment of the response of floating wind turbines under extreme wave conditions, structure stability and survivability is of utmost importance in the design and implementation. The experimental upwind horizontal axis floating wind turbine on a tension leg platform (TLP) setup was validated with the strongly coupled partitioned six degree-of-freedom rigid body motion solver (Chow and Ng 2016). After tuning of the unknown variables such as the tendon stiffness and damping coefficients with the decay tests, the system ran with the coupled fluid-motion numerical solver resulted in accurate estimations of the natural frequencies and damping ratios. Together with a modified restrain system to model the tendons, the response of the floating wind turbine under regular and focused waves simulations were found to be well-predicted. A stability analysis was performed to determine the iterations that should be ran every time step. The median of the time steps converged within 8.7 iterations.